Erosive wear of natural gas pipes due to high velocity jet impact: Physical examination and experimental study - Majid Z.A.; Mohsin R.; Yusof M.Z. (Penerbit UTM Press, 2023)
A sequential failure of API 5L X42 (NPS8) carbon steel and SDR 17 medium density polyethylene (MDPE) pipes towards the high pressure water pipe was studied. Pipe's failed specimen was physically examined and experimental testing was conducted by using high speed water jetting facility towards a similar NPS8 pipe specimen. High pressure water jet impact from leaked water pipe forms highly erosive water-soil slurry, causing severely damaged on NPS8 carbon steel pipe surface. Thus, it causing substantial losses of pipe coating materials and subsequent rapid thinning of pipe body occurred. Furthermore, weaker ground support causes instability to the MDPE pipe and leads to vertical descend towards high speed gas jet region exerted from failed NPS8 pipe. High impact gas jet physically hit the MDPE pipe at its opposite direction causing its rapid erosion. Penerbit UTM Press, Universiti Teknologi Malaysia.